INFLUENCE OF EMBRYOTOXIC FACTORS ON THE FETUS - Utamuradova Nigora Abdurakhmanovna (Western European Studies, 2024)
During the twentieth century, human life expectancy in Central Europe increased from 45 to 75 years. This dramatically changed situation cannot be attributed solely to improvements in the field of social hygiene (improved quality of drinking water and other environmental factors). Experts believe that the increase in average life expectancy is largely due to the use of drug treatment for patients
Keywords: embryotoxic factors; fetus; electromagnetic